THE GOD OF THE GAPS - Vanden Auweele, Dennis (Journal of Dharma, 2011)
Our present age has, especially in the West, an explosion of publications by scholars of various backgrounds, each in their own way, propagating some form of atheism. Some of the more outspoken among these are Daniel Dennett, 1 Richard Dawkins.’ Christopher Hitchens/ Sam Harris," Victor Stenger.i David Mills6 and Gref Graffin.These authors engendered, especially in Northern America, a lively debate on the value, the scientific foundation and the rationality of religion.